IMPLEMENTASI MODEL EDUKASI PENGEMBANGAN KETERAMPILAN ZERO WASTE PADA LAPAK PERUBAHAN NUSANTARA KELURAHAN JATI SAMPURNA BEKASI SELATAN - Tina Rosa; Nurminingsih; Ravel Anwar (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
This study aims to evaluate the effectiveness of the implementation of the educational model in the development of zero waste skills at the Change Archipelago stall in Jati Sampurna Village, South Bekasi. The research approach is descriptive qualitative research with data collection techniques through observation, interviews, and questionnaires. The results showed that the profile of the changes in the archipelago stalls in the Jati Sampurna Village were stalls that sold various types of used goods and had implemented the zero waste principle well. However, the zero waste skills possessed by lapak members still need to be improved. Implementing an educational model for developing zero waste skills at the Simpan Nusantara lapak has proven to be effective in increasing the zero waste skills of lapak members. Obstacles in implementing the educational model include the lack of support and awareness from lapak members. Based on the research results, it is suggested that the implemented educational model can be improved by involving experts and zero-waste practitioners. The Archipelago's Change Static is expected to continue applying the zero waste principle and strengthen customer communication. Future research can explore a more appropriate educational model to improve zero waste skills in lapak members and involve a more comprehensive sample.